Gene pool of meat cattle in Ukraine - Prudnikov , V. H.; Kryvoruchko , Yu. I.; Kolisnyk , O. I. (Scientific Progress & Innovations, 2019)
The aim of the article is to study the topical issue as to the modern state of the gene pool of meat cattle breeding in Ukraine. Methods of the research. The basis of the research was the data of the state register of pedigree business subjects in livestock farming for the period 2014–2017 in Ukraine, and their perfect systemic analysis. The research results. The article presents the results of research on the current state of the domestic gene pool of cattle meat breeds, the number of breeding plants and reproducers of their breeding, offer solutions of the problem of overcoming the crisis and preserving the breeding resources of the meat cattle industry. It has been established that the number of pedigree farms engaged in breeding meat cattle decreases every year. Of the 90 pedigree plants and breeding reproducers, only 64 remained, that is, decreased by 28.9 %. In 2015, the breeding reproducer of meat breed Piemontese lost its status and ceased to exist. The number of farms breeding livestock of Volyn meat breed has sharply decreased from 25 to 13, Simmental meat breed – from 8 to 4, Polissya meat breed – from 12 to 9; gray Ukrainian breed is on the verge of disappearing. The elements of scientific novelty. The dynamics of the number of meat cattle among the breeds in Ukraine, the number of breeding plants and reproducers engaged in their breeding in 2014–2017 were studied, and the suggestions as to how to overcome the crisis situation in the domestic branch of meat cattle breeding were made. Practical importance. There is the urgent need to solve the problem of preserving the pedigree resources of meat cattle breeding of Ukraine at the state level, namely to stop the decline of meat livestock population, to start financing the selection programs in breeding, improving and preserving breed resources. It will enable not to lose the domestic branch of meat cattle farming and have a significant gene pool of meat breeds.